MHC-associated Baylisascaris schroederi load informs the giant panda reintroduction program. (August 2020) - Zhu, Ying; Grueber, Catherine; Li, Yudong; He, Ming; Hu, Lan; He, Ke; Liu, Hongyi; Zhang, Hemin; Wu, Honglin
Abstract: Reintroducing captive giant pandas ( Ailuropoda melanoleuca ) to the wild is the ultimate goal of their ex situ conservation. Choosing higher fitness candidates to train prior to release is the first step in the giant panda reintroduction program. Disease resistance is one important index of individual fitness and presumed to be related to variation at major histocompatibility complex genes (MHC). Here, we used seven polymorphic functional MHC genes ( Aime -C, Aime -I, Aime -L, Aime -DQA1, Aime -DQA2, Aime -DQB1 and Aime -DRB3) and estimate their relationship with Baylisascaris schroederi (Ascarididae) infection in giant panda. We found that DQA1 heterozygous pandas were less frequently infected than homozygotes. The presence of one MHC genotype and one MHC allele were also associated with B. schroederi infection: Aime -C*0203 and Aime -L*08 were both associated with B. schroederi resistance. Our results indicate that both heterozygosity and certain MHC variants are important for panda disease resistance, and should therefore be considered in future reintroduction programs for this species alongside conventional selection criteria (such as physical condition and pedigree-based information). Graphical abstract: Image 1 Highlights: MHC heterozygous pandas were less frequently infected by Baylisascaris schroederi than homozygotes . Presence of Aime -C*0203 and Aime -L*08 are associated with Baylisascaris schroederi resistance . MHC types are important for panda parasite resistance .